2017
DOI: 10.1021/acs.inorgchem.7b01230
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Mechanism of Formation of Hydride–Sulfide Complexes of Iron

Abstract: Iron-sulfide complexes with hydride ligands provide an experimental precedent for spectroscopically detected hydride species on the iron-sulfur FeMoco of nitrogenase. In this contribution, we expand upon our recent synthesis of the first iron sulfide hydride complex from an iron hydride and a sodium thiolate (Arnet, N. A.; Dugan, T. R.; Menges, F. S.; Mercado, B. Q.; Brennessel, W. W.; Bill, E.; Johnson, M. A.; Holland, P. L., J. Am. Chem. Soc. 2015, 137, 13220–13223). First, we describe the isolation of an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…323 This C−S bond cleavage reaction was suggested to proceed through the generation of a short-lived alkyl radical which abstracts a hydrogen atom from Fe, based on a radical-clock experiment using a cyclopropyl-methanethiolate anion. 324 The hydride ligand in 117 was found to function as a base to deprotonate a terminal alkyne (mtolyl)CCH to furnish a terminal acetylide complex or as a hydride donor to insert into CO 2 to give a bridging formate complex. 323 As anticipated from the coordinative unsaturation in 114, its Fe centers were found to accommodate various N-donor ligands, e.g., hydrazines, ammonia (NH 3 ), and NCMe.…”
Section: N 2 Hmentioning
confidence: 99%
See 1 more Smart Citation
“…323 This C−S bond cleavage reaction was suggested to proceed through the generation of a short-lived alkyl radical which abstracts a hydrogen atom from Fe, based on a radical-clock experiment using a cyclopropyl-methanethiolate anion. 324 The hydride ligand in 117 was found to function as a base to deprotonate a terminal alkyne (mtolyl)CCH to furnish a terminal acetylide complex or as a hydride donor to insert into CO 2 to give a bridging formate complex. 323 As anticipated from the coordinative unsaturation in 114, its Fe centers were found to accommodate various N-donor ligands, e.g., hydrazines, ammonia (NH 3 ), and NCMe.…”
Section: N 2 Hmentioning
confidence: 99%
“…It should be noted that the Fe I state is unusual in iron–sulfur cluster chemistry and only 116 and [{(PhBP 3 )­Fe} 2 (μ-S)] 2– (PhBP 3 = PhB­(CH 2 PPh 2 ) 3 ) are unambiguously identified examples of sulfide-bridged Fe I 2 complexes, with the excception of NO complexes for which assignment depends on the formalism of the NO ligands. A relevant Fe II 2 complex with one bridging sulfide and one bridging hydride, [Na]­[(L 1 Fe) 2 (μ-S)­(μ-H)] ( 117 ), was synthesized from the reaction of a hydride complex [L 1 FeH] 2 with sodium dodecanethiolate (NaSC 12 H 25 ), where homolytic cleavage of a C–S bond took place to generate the bridging sulfide . This C–S bond cleavage reaction was suggested to proceed through the generation of a short-lived alkyl radical which abstracts a hydrogen atom from Fe, based on a radical-clock experiment using a cyclopropyl-methanethiolate anion . The hydride ligand in 117 was found to function as a base to deprotonate a terminal alkyne ( m -tolyl)­CCH to furnish a terminal acetylide complex or as a hydride donor to insert into CO 2 to give a bridging formate complex …”
Section: Sulfur-supported Transition Metal Complexes In N2 Chemistrymentioning
confidence: 99%
“…Treatment of complex 1 or 2 with strong reductant KC 8 at room temperature facilely generated thiolatebridged diiron complex 3 or dicobalt complex 4 in high yields. Similar to other iron-sulfur clusters supported by β-diketiminate ligands, [16] complexes 3 and 4 are also both paramagnetic species. In their 1 H NMR spectra, a series of obviously broadened signals appear in an unusual range from À 10 to 15 ppm.…”
Section: Synthesis and Characterization Of Mononuclear Iron Precursor...mentioning
confidence: 53%
“…Given that oxidation of [ 1–MP ] + triggers alkyl-group migration from Fe to S, we were interested to learn if the reverse reactionalkyl-group migration from S to Fewould occur upon reduction of [ 2 ] 2+ (Figure ). Such a finding would build on prior work that has established the cleavage of S–C bonds at Fe–thiolate complexes, though in these examples the organic groups were lost as radicals instead of recombining with the complex to form an Fe–C bond. In the present study, we observed that treatment of [ 2 ]­[PF 6 ] 2 with 1 equiv Cp 2 Co in o -DFB at −35 °C for 5 min resulted in a color change to dark brown.…”
Section: Resultsmentioning
confidence: 94%